Predictive value of hemostatic markers for complicated acute appendicitis in children: a key role for international normalized ratio - Hernández-Meza, Emmanuel; Lozano-Rodríguez, Luis A.; Astorga-Haro, Carlos E.; Ibarra-Fierro, Armando; Galván-Ruíz, Vanessa G. (International Journal of Research in Medical Sciences, 2025)
Background: Acute appendicitis (AA) is a common surgical emergency worldwide. The primary adverse event in patients with AA is the progression to complicated appendicitis. Although various scoring systems exist to improve diagnostic accuracy, there remains a need for simple, inexpensive, and readily available biomarkers. This study aims to identify the value of coagulation tests as a predictor of complicated acute appendicitis in pediatric patients. Methods: We conducted a retrospective, cross-sectional study to evaluate the diagnostic performance of hemostatic markers. The study included medical records from pediatric patients who underwent an emergency appendectomy at our general surgery department between January 2022 and July 2022. Results: A total of 84 patients were included, with an incidence of complicated acute appendicitis (CAA) of 35.71%. Receiver operating characteristic (ROC) curve analysis revealed good diagnostic performance for INR (AUC=0.803; 95% CI 0.697-0.908; p<0.001) and acceptable performance for PT (AUC=0.774; 95% CI 0.667-0.881; p<0.001) and fibrinogen (AUC=0.769; 95% CI 0.666-0.872; p<0.001). Partial thromboplastin time (PTT) did not show significant predictive value. Conclusions: International normalized ratio (INR) is a valuable and readily available biomarker for predicting complicated AA in the pediatric population. Fibrinogen and PT also demonstrate significant, albeit lower, predictive utility. These hemostatic markers can serve as objective tools to aid in early risk stratification and optimize clinical management.